Fairy-tale enchantments - Vaz da Silva, F. (2021)
More than two decades ago the folklorist Isabel Cardigos remarked that the hinge of fairy tales is the cyclical movement in and out of enchantment. I feel that this insight is important, and I propose to brieﬂy explain my understanding of it. First, I mention the importance of using allomotifs to bring out the folk metaphors in fairy tales. Then, I discuss a basic symbolic pa﬒ern of enchantments at the core of fairy tales. Overall, I add to Vladimir Propp’s statement that the most complete fairy tale is a heroic quest the proposition that the irreducible core of fairy tales hinges on feminine maturation. Along the way, I discuss some metaphors suggestive of the lunar template at the core of fairy tales.